THE EFFECTS OF BABY MASSAGE ON BOUNDING ATTACHMENT OF PRIMIPARA MOTHER IN BPM KECAMATAN PERIUK TANGERANG - Rika Aprianti (UPT Penerbitan Universitas Jember, 2017)
Background: Baby massage is a touch therapy of the skin by hand. Infant massage is believed to increase brain stimulus, optimize the growth process, smooth blood circulation, to stimulate digestive system function, and even increase endurance. Also, can build Bounding Attachment. Nurses make promotions to reduce infant mortality. For that need the existence of intensive education so that can build good bonding attachment. Methods: This research design is Quasi-Experiment with nonrandomizer pre-test post-test with the control group. The number of samples was 6 as the intervention group and 6 as the control group. The research variables are knowledge and attitude of Bounding Attachment before education and knowledge and attitude of Bounding Attachment after education. Data were collected by questionnaire. Results: Based on the result of research there is the influence of education to mother primipara to knowledge and attitude of Bounding Attachment, with t independent statistic, with pValue = 0,003. In conclusion, there is an influence of education giving the influence to increase knowledge and attitude of primipara mother of intervention group in doing bounding attachment. Conclussion: give education about baby massage in primipara mother, because it is very effective in building Bounding Attachment. Keywords: Primipara, Education, Bounding Attachment, Baby Massage